A simple model for fruit tree shaking harvest - Láng, Z. (International Journal of Horticultural Science, 2007)
A tree structure model was composed of trunk and main roots. It included a mass, spring and damping element, all of them reduced to the external end of the main roots. The model parameters, such as virtual turning centre, reduced mass, spring constant and clamping coefficient were measured on a real cherry tree. The model was than virtually shaken at 80 cm trunk height and acceleration and displacement amplitudes versus shaking frequency were calculated. The real cherry tree was shaken also at 80 cm trunk height by an inertia type shaker machine and the same data were recorded. The acceleration amplitude vs. frequency and displacement amplitude vs. frequency functions were similar for the virtual and real tree which proves the ability of the model. Power demand and specific power demand was then calculated in function of shaking frequency. The diagrams show that the shaking frequency of 12-14 Hz, of the practice is not the most efficient concerning amplitude, but is probably necessary from the point of view of acceleration needed to detachment of fruits.